How has COVID-19 lockdown impacted smoking? A thematic analysis of written accounts from UK smokers. Issue 1 (7th January 2022) - Grogan, Sarah; Walker, Lucy; McChesney, Gillian; Gee, Ivan; Gough, Brendan; Cordero, Maria I.
Abstract: Objective . This study was designed to investigate UK smokers' accounts of impacts of COVID-19 on their smoking, to develop implications for supporting smoking cessation. Design . One hundred and thirty-two smokers aged 19-52 years (mean age 25 years), recruited through an advert distributed through social media and a dedicated Twitter page, completed an anonymous online questionnaire. Main Outcome Measures . Smokers produced written accounts of how COVID-19 had impacted their smoking. Responses were of unlimited length and completed online 22 nd May-22 nd June 2020 during UK COVID-19 lockdown. Results . Inductive thematic analysis generated three themes: i) increased smoking as a coping mechanism to deal with anxiety, boredom, stress, and anger in COVID-19 lockdown; ii) lockdown as enabling quitting through lifting social barriers and enabling a focus on health benefits; and iii) no change, avoiding Government/media COVID-19 information due to disbelief, lack of trust, and perceptions of bias. Conclusions . Results demonstrate a need for credible public health messaging on COVID-19 risk aimed at smokers. Implications for supporting smoking cessation are discussed, including maintaining quitting in those "social smokers" who quit during lockdown, and support on stress-management and emotion regulation in those who use smoking as a way to cope with stress, anger, and boredom.